2017
DOI: 10.3945/jn.116.241521
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Food Intake Is Associated with Reproductive Hormones and Sporadic Anovulation among Healthy Premenopausal Women

Abstract: Background: Dairy food intake has been associated with infertility; however, little is known with regard to associations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 37 publications
3
16
0
1
Order By: Relevance
“…Despite lack of sufficient evidence for identification of the underlying mechanisms involved, it can be assumed that this lower rate of decline in AMH may indicate either the lower rate of follicular recruitments, by affecting ovulation or menstrual cycle, or higher production of AMH from granulosa cells with higher intakes of dairy foods. Previous findings of higher risk of sporadic anovulation with higher intakes of some types of dairy foods, including cream and yoghurt [29] and higher risk of anovulatory infertility with higher intakes of low fat [30] support the assumption that dairy products may slow follicular reduction by increasing anovulatory menstrual cycles. However, the association was not seen for total dairy intakes and high fat dairy.…”
Section: Discussionmentioning
confidence: 93%
“…Despite lack of sufficient evidence for identification of the underlying mechanisms involved, it can be assumed that this lower rate of decline in AMH may indicate either the lower rate of follicular recruitments, by affecting ovulation or menstrual cycle, or higher production of AMH from granulosa cells with higher intakes of dairy foods. Previous findings of higher risk of sporadic anovulation with higher intakes of some types of dairy foods, including cream and yoghurt [29] and higher risk of anovulatory infertility with higher intakes of low fat [30] support the assumption that dairy products may slow follicular reduction by increasing anovulatory menstrual cycles. However, the association was not seen for total dairy intakes and high fat dairy.…”
Section: Discussionmentioning
confidence: 93%
“…In the NHS-II study no relation was found between total dairy intake and risk of ovulatory infertility, however anovulatory infertility was positively associated with low-fat and inversely associated with high-fat dairy intake (46). Similarly, the Biocycle study (125) reported that sporadic anovulation was more common among women consuming higher amounts of cream and yogurt. In the same study, total and low-and high-fat dairy food intakes were associated with a 5% reduction in serum E 2 concentrations, and total and high-fat dairy food intakes were positively associated with serum lLH.…”
Section: Proteinmentioning
confidence: 95%
“…Changes in hormone levels resulting from dairy product intake were also observed in studies conducted in people. According to Kim et al [61] each increase in the consumption of dairy products by one serving per day was associated with the reduction in serum estradiol concentrations by 4.6% and free estradiol by 4.0%. Conversely, the highest total dairy intake was linked to an increase in LH concentrations by 2.9% over the whole cycle compared to the lowest intake.…”
Section: Dairy Products Versus Ovulation and Fertility In Womenmentioning
confidence: 99%